Avaliação externa: apropriação e usos pelos gestores educacionais de três municípios maranhenses - Panico, Roberta Leite (2017)
In the last years the external evaluation has occupied central place in the educational policies of the nation, the states and the cities. Many studies have been published and mention the growing initiative of the use of external evaluation by educational management of cities. However, the use of external evaluation by municipal networks still presents many challenges, since its use does not always turn into improvement for student learning. In the light of this context, the present study aims to identify the appropriation and uses of external evaluation by educational managers, specifically the professionals from the education departments of the cities of Miranda do Norte, Santa Inês and Monção, in the state of Maranhão, which participated for two years in the "Evaluation and Learning" training program, a public-private partnership between the Fundação Itaú Social (FIS) and the Civil Society Organization for Public Interest Comunidade Educativa CEDAC. Intending to understand the possible uses and appropriation of the external evaluation by the teams of the education departments that have undergone the formative process, this study aims to contribute to a more in-depth discussion about these uses and about the training of educational managers in this theme. This is a qualitative research that used as a methodological procedure the content analysis from the reports of five participants of the training program, captured through semi-structured interviews. From the collected data, it was possible to identify uses and appropriations of the external evaluation by the educational managers, related to two categories. One category refers to practices that qualify data from external evaluation and the other refers to practices that organize and structure the work on the network